Pengaruh Edukasi Pasar Modal, Norma Subjektif Dan Literasi Keuangan Terhadap Keputusan Berinvestasi Saham - Wahyuni Amalia Putri; Eja Armaz Hardi; Neneng Sudharyati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This study aims to determine and analyze the effect of capital market education, subjective norms and financial literacy on stock investment decisions for FEBI investors at UIN STS Jambi. The method used in this study is a quantitative method, and the data analysis method used is the coefficient of determination test. The sample in this study was 95 samples of FEBI UIN STS Jambi investors who were recorded in the Islamic investment gallery. The results showed that partially education on the capital market had no significant effect on stock investment decisions, subjective norms and financial literacy had a positive effect on stock investment decisions. Simultaneously it shows that the variables of capital market education, subjective norms and financial literacy have a significant effect on the investment decisions of FEBI investors at UIN STS Jambi. The results of the calculation of the coefficient of determination show that the variables of knowledge, risk and investment motivation, capital market education, subjective norms and financial literacy have an influence of 45.8% and the remaining 54.2% is influenced by other variables outside this study.